Housing Policy in Crisis: An International Perspective - Fields, Desiree J.; Hodkinson, Stuart N. (Housing policy debate, 2018)
Introduces a special issue of this journal that critically explores the role of policy in both generating and potentially addressing the instability faced by housing systems globally.